Features of the interconnection between the results in the Olympic all-round between different disciplines of rock climbing in boys aged 16-17 on the results of the 2017 World Championship - N.V. Uvarova; Zh.L. Kozina; N.A. Kolomiets; K.V. Tieniakova (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The purpose of this study: the identification of the relationship between certain types of sport climbing in the Olympic discipline rock climbing "all-round" at boys 16-17 years old. Material and methods. The study was attended by 16 -17-year-old athletes, youth championships in 2017 in Innsbruck (Austria). Results of the analysis of 79 youngsters of climbers aged 16-17 years, representing 36 countries of the world. It was analyzed the results of the all-round, shown by the participants of the competition, and time passing the reference tracks on the speed. In the framework of the conducted research, protocols of competitions from all-rounders were analyzed, and to the points scored by each participant of the competition was added his time passing the route to speed. Results 1. Between results in certain types of rock climbing and all-round, reliable interrelationships were found between the results in the "Multiplayer" and "Difficulty" types (r = 0.69, p <0.05), Multiplayer and Speed (r = 0.66, p <0.05), "Multiplayer" and "Bouldering" (r = 0.69, p <0.05). The dispersion analysis of the influence of the results in certain types of rock climbing on the result in the all-round showed the presence of reliable dependence of points in the all-round on the results in the disciplines "Bouldering" (p <0,05), "Difficulty" (p <0,05) and from the combined interaction of results in These types of climbing on the result in all-round (p <0,05). There was no significant influence of the result in the discipline "Speed" on the result in all-round (p> 0,05). Conclusion. For a high result in all-round competition, athletes who specialize in the disciplines "Difficulty" and "Bouldering" are more likely to have more chances, as the results in these disciplines are interrelated. For athletes who specialize in the "Speed" discipline, achieving a high score is a difficult task, since the results in the discipline "speed" are not related to the results in the disciplines "Difficulty" and "Bouldering" and do not significantly affect the outcome in all-round.